Review of Altman, W. The Guardians in Action: Plato the Teacher and the Post-Republic Dialogues from Timaeus to Theaetetus (2016) - Engler, M. R. (Revista Archai, 2019)
Review of Altman, W. The Guardians in Action: Plato the Teacher and the Post-Republic Dialogues from Timaeus to Theaetetus (2016)